Silicon Release Characteristics of Graded Levels of Fly Ash with Silicate Solubilizing Bacteria and Farm Yard Manure in Soil Under Submergence - GHOUSE PEERA, S. K. PEDDA; BALASUBRAMANIAM, P.; MAHENDRAN, P. P. (Indian Journal of Hill Farming, 2015)
An incubation experiment was conducted to study the release characteristics of silicon from native soil and applied sources viz, Fly Ash (FA), Silicate Solubilizing Bacteria (SSB) and Farm Yard Manure (FYM). The soil for incubation study collected from Eastern block of Agricultural Engineering College and Research Institute which is low status of plant available silicon. The treatments consist of graded levels of FA viz., 0, 12.5, 25, 37.5 and 50 g/kg of soil with and without SSB and FYM. Six sets of plastic containers consist of 40 numbers in each set to accommodate 20 treatments with 2 replications under Factorial Completely Randomized Design for 15, 30, 45, 60 75 and 90 days duration of incubation. The calculated quantity of FA, SSB and FYM was applied to each container containing 10g of soil and mixed thoroughly. Extracted plant available Si by using 1N NaOAc (pH 4.0) and estimated calorimetrically at 15 days interval i.e 15, 30, 45, 60 75 and 90 days duration of incubation. The results revealed that among different treatments, addition of SSB + FYM resulted a consistent increase of N NaOAc (pH 4.0) extractable Si from 144.7 mg per kg to 272.2 mg per kg during 15th to 60th days after incubation, thereafter a slight decline in N NaOAc (pH 4.0) extractable Si was observed up to 90 days. Among the different treatments the application of SSB +FYM recorded the highest N NaOAc (pH 4.0) extractable Si of 272.2 mg per kg at 60th day followed by FYM (258.0 mg per kg) on 75th day of incubation. The control recorded the least N NaOAc extractable Si throughout the incubation period. Imposition of graded levels of fly ash and their interaction with various sources viz., SSB, FYM and SSB+FYM have shown significant variations in the N NaOAc (pH 4.0) extractable Si throughout the incubation period. Imposition of fly ash @50 g kg-1 of soil with SSB + FYM depicted more release at 15,30,45,60 and 75 days after incubation which was on par with addition of fly ash @25 g kg-1 of soil at 90 days after incubation.